(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Today, culture became an integral part of international politics and takes a vital role in the world arena. Many countries use cultural diplomacy to gain recognition of their cultural heritage and opportunity to encourage the way the people achieved. This article highlights the importance of using «Soft power» in the countries along the New Silk Road. The «Soft power» here is considered to be a force that can be used to exchange cultural and political values around the world and with foreign policy. The article also focuses on the «One Belt – One Way» project, which is a channel that differentiates the values of Chinese culture throughout the world. Along with other countries of Central Asia, Kazakhstan being the closest geopolitical and geo-economic region, contributes to strengthening and spreading the power of the global influence of cultural and spiritual values, technology, etc. This article discusses China’s active participation in the economic life of other Central Asian countries, and using «soft power» there is a decrease in demographic and economic danger from nearby countries. «Soft power» is seen here as a factor that enables the exchange of cultural and political values and foreign policy around the world. The article is also devoted to the project «Bir Beldeu – Bir Jol», which is the channel for the dissemination of the values of Chinese culture throughout the world. Key words: Culture, New Silk Road, Soft Power, Cultural Values, Confucius Institute, Globalization, younger generation.